احكام الحضانة في قانون الاسرة الجزائري على ضوء الفقه الاسلامي - زادم خديجة; بعيط كريمة; د/ زيغمي نعيمي (جامعة عمار ثليجي الاغواط, 2016)
ملخصالمذكرة: في عصر الأئمة المجتهدين اتسعت دائرة الرأي، بحيث جدت سبل أخرى للاستدلال والاستنباط كأقوال الصحابة-رضي الله عنهم- وشرع من قبلنا والمصالح المرسلة،والاستصحاب، وسد الذرائع، وعمل أهل المدينة، وماإلى ذلك من الدلائل التي بنى عليها بعض المجتهدين اجتهادهم،مما كان له أكبر الأثرفي تنمية الفقه الإسلامي،واتساع دائرته، حتى يواجه كل متطلبات الحياة . ومن هذه الدلائل« سد الذرائع» باعتبارها وسيلة من وسائل الوصول إلى حكم شرعي، سواءكان مباحا أو ممنوعا، فهو أصل من أصول الإسلام يبنى عليه كثيرمن الأحكام، إباحة أو حظرا، لما يترتب على ذلك من جلب مصلحة أو دفع مفسدة . والإسلام - دائما - ينظر إلى مقاصد الأشياء ومآلاتها، حتى يضبط تصرفات الناس في إطار من الحق والعدل، وصون الحرمات . ومن هنا نجده ينهى عن أشياء ليست في الأصل محرمة وإنما تؤدي إلى محرم قطعا أو غالبا، كما أنه قد يبيح المحرم في بعض الظروف الخاصة، حتى لو ترتب على ذلك بعض المفاسد، إلا أنها في مقابلة ماهو أعظم فسادا أهون وأقل. Abstract At the age of the Imams hardworking people circle (opinion) so created other ways to replac And the elicitation like companion -PBUH- says and he stared by us,And the sent interests ligistation ,And fill SAD DARAIA , And the work of the people of Madina ,And so forth from evidence onwich has had the creates impact on the development of Islamic jurisprudence and the breadth of his constituency,even face all the requirement of life. And from this evidence SAD DARAIA. As one of the means access to legal judgment.Whether it is permissible or for bidden.He asset of Islam built on upon many of the provision divulging that of bringing interest or push spoiler. And Islam always look to purposes of the things and what they mean ,so seize the action of people in the framework of right and Justice, And the safeguarding of privacy. And from here,We find forbid thingsthat are not originally prohibited. But lead to forbidden definitely or often. It many also entitles forbidden in some special circumstances. Even some of the consequent evils. But she said in facing up. What is the greatest havac easier and Less.